STUDENT PERCEPTION IN USING MADLIPZ IN AN ENGLISH ORAL COMMUNICATION CLASSROOM: A CASE STUDY IN UNIVERSITI MALAYSIA SABAH, MALAYSIA - Anna Lynn Abu Bakar; Wan Hurani Osman; Sabariah Abd. Rahim; Nor Dawirah Rahman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The English language is seen as an important medium of communication between people especially in higher institutions in Malaysia and also in the working world. Thus, a lot of effort has been put in to producing students who are competent in communicating effectively in a different social and professional context. One of the ways in enhancing students’ proficiency in English is by using Madlipz. Madlipz is an application that could be downloaded to the handphone. The application allows students to dub their voices and create their own dialogue or monologue based on the video clips that they chose. With regards to this, this study looks into the use of MadLipz in enhancing students’ proficiency in English. Students who took Oral Communication in English were involved in this study. A mix-method approach has been applied to collect data for the purpose of the study. The findings of this study revealed that not only has MadLipz improved students’ pronunciation in English, but the application has also improved students’ self-esteem and confidence level to speak English.